Parallel processing in Compute Unified Device Architecture (CUDA) for energy saving glass - Shibghatullah, Abdul Samad; Xia, Khoo Wen; Azmin, Farah Ayuni; Mohd Johar, Fauzi (Publications International, 2014)
Energy saving glass is used to keep the warmth and temperature of a building instead of using thermal radiator or machine to generate the heat all the time during winter. Yet the coating structure of the glass is mostly in regular shape such as tripoles and circular with a very small size that limits the useful signal such as wireless signal and radio frequency to pass through. One way to allow more useful signals to go through the glass is by using complex shape coating structure. In order to develop a complex coating structure, genetic algorithm technique is used in this research. However, genetic algorithm require a fast processing speed in order to cope with the process of creating new chromosome from the population and undergoes the selection, crossover and mutation operation processes. Hence parallel processing is needed to overcome this problem with the use of both CPU and GPU to eliminate the need of purchasing high performance CPU and the needs of adding additional repeaters to increase the wireless signals. The coating structure will be presented in binary bits in a text file that shows the best chromosome. The result will be analyzed in a simulation tool that uses to check for the signal transmission efficiency and rate loss.